Development of a Web-Based Tourism and Culinary Promotion Information System Using the Waterfall Method: A Case Study of Aceh - Ilham; Rita Novita; Khairuman (LPPM Politeknik Aceh Selatan, 2026)
The rapid advancement of information technology has significantly influenced various sectors, including tourism and culinary industries, which are key drivers of regional economic growth. However, the promotion of Aceh’s tourism and culinary potential remains less effective due to the limited use of digital platforms. This study aims to design and develop a web-based information system for promoting Aceh’s tourism and culinary sectors as part of a digital investment strategy for the Aceh Investment and One-Stop Service Office (DPMPTSP). The system was developed using the Waterfall model through five stages: requirements analysis, system design, implementation, testing, and maintenance. The prototype was built using React.js for the front end and MySQL as the database; however, not all components are dynamic some website contents remain static to suit the needs of the institution and the scope of this research. The system provides integrated information about tourist destinations, traditional culinary products, and local events. Based on Blackbox testing, all features functioned properly according to specifications, and usability evaluation showed that the website is easy to use, efficient, and visually appealing. This research demonstrates that a semi-dynamic web-based information system can be an effective digital solution for promoting regional tourism and culinary potential while enhancing Aceh’s digital investment attractiveness.